New Candidate Predisposition Genes for Hereditary Breast Cancer: SLIT3, CREB3, USP39 - Kirill Zagorodnev; Alexandr Romanko; Anna P. Sokolenko; Ilya Bizin; Ekaterina S. Kuligina (Medical Laboratory Technology Journal, 2021)
Breast cancer is the most common type of malignant neoplasm in women. BRCA1 and BRCA2 are the most commonly mutated genes, but only up to 30% of hereditary breast cancer cases are attributed to alterations in these genes. A large proportion of genetic causes of hereditary breast cancer remains unknown. Thus, the search for new hereditary mutations and establishing a genetic alteration in each case of hereditary breast cancer is a clinically significant task; be the goal of our research. Next-generation sequencing (NGS) allows for simultaneous analysis of hundreds to thousands of genes at one time. We analyzed the genetic material of 49 patients of the northwest Russian population with clinical signs of hereditary breast cancer and identified new mutations associated with hereditary breast cancer. Research results show two missense mutations - SLIT3 p.Arg154Cys, CREB3 p.Lys157Glu, and truncating mutation - USP39 c.*208G>C. Research conclusion; The identified mutations can explain only a tiny fraction of hereditary breast cancer cases (0.7% to 1.1%). The next step to increase the practical value of the detected alterations should be the analysis of biological characteristics of tumors in carriers of these mutations that can potentially become a target for chemotherapy.